PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA PESANTREN TERHADAP MOTIVASI KERJA GURU - KURNIA DEWI PERMATASARI; FATHORRAHMAN; TIN AGUSTIN K (AKADEMIKA, 2023)
This study aims to analyze the Principal's Leadership and Islamic Boarding School Culture on Teacher Work Motivation at Darul Lughah Wal Karomah Junior High School Kraksaan Probolinggo. This type of research is a quantitative research. In this study, primary data was used and carried out by observation and questionnaires at Darul Lughah Wal Karamah Middle School, Kraksaan Probolinggo. Respondents used in this study were the teachers and staff of SMP Darul Lughah Wal Karomah Kraksaan Probolinggo, amounting to 47 people. The sampling technique used is a saturated sampling technique. Data analysis used Descriptive Analysis, Research Instrument Test, Hypothesis Testing, Classical Assumption Test, Multiple Linear Regression Analysis, and Coefficient of Determination Analysis. The results of this study indicate that the variables of leadership and culture simultaneously have a positive and significant effect on the variable of work motivation at Darul Lughah Wal Karomah Junior High School Kraksaan Probolinggo. While the results of the partial test with the t-test showed that leadership and culture variables had a positive and significant effect on the work motivation variable at Darul Lughah Wal Karamah Middle School, Kraksaan Probolinggo.